DYNAMICS OF HEALTH DISPUTE RESOLUTION THROUGH RESTORATIVE PROCESSES - Gunawan Widjaja (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
Healthcare dispute resolution is a complex issue that often involves tensions between patients, medical personnel and healthcare institutions. Restorative processes have emerged as an alternative approach that focuses on restoring relationships and achieving fair solutions through dialogue and mediation. In the context of healthcare disputes, this method offers a more humane solution than the more confrontational approach of litigation. This article discusses the dynamics of dispute resolution through restorative processes, including its advantages, challenges and potential in creating an efficient dispute resolution system centred on restorative justice. It concludes that restorative approaches can reduce conflict, accelerate the resolution process, and restore public trust in health institutions, provided that they are properly implemented and supported by adequate regulations.